Lithium bromide-water absorption chiller with integrated compression for performance enhancement - M’madi Hassane Mohamed; Filali Baba Yousra; Al Mers Ahmed; Noureddine Boutammachte; Bakkas M'bark (EPJ Web of Conferences)
Absorption refrigeration systems offer a sustainable alternative to vapor compression cycles by exploiting low-grade thermal energy. However, their low coefficient of performance (COP) limits their competitiveness in high-efficiency cooling applications. To overcome this limitation, a hybrid approach integrating a mechanical compressor between the evaporator and absorber in a double-effect absorption cycle has been proposed. This study investigates the thermodynamic feasibility of this configuration using a lithium bromide-water solution as the working pair. The analysis of key parameters, including generator temperature, condenser temperature, compression ratio, and evaporation temperature, highlights a significant improvement in the performance of the hybrid system compared to the conventional absorption cycle. At a generator temperature of 85°C, the integration of the compressor results in a COP increase ranging from 22% to 55%, depending on the adopted compression ratio. This improvement is particularly pronounced for higher Pr values, demonstrating the compressor’s effectiveness in optimizing heat and mass transfer within the absorber. These findings provide a solid foundation for the further development of high-efficiency refrigeration systems, particularly for integration with renewable heat sources.